The prospective associations of 24-hour movement behaviors and domain-specific activities with executive function and academic achievement among school-aged children in Singapore - Padmapriya, Natarajan; Bernard, Jonathan Y.; Tan, Sarah Yi Xuan; Chu, Anne H. Y.; Goh, Claire Marie Jie Lin; Tan, Shuen Lin; Shek, Lynette P.; Chong, Yap Seng; Tan, Kok Hian; Chan, Shiao-Yng; Yap, Fabian; Godfrey, Keith M.; et al. (Frontiers in Public Health, 2024)
Background: Physical activity (PA), sedentary behaviour (SB), and sleep are collectively referred to as 24-hour movement behaviours, which may be linked to cognitive development in children. However, most of the evidence was based on cross-sectional studies and/or solely relied on parent-reported information on children’s behaviours, and it remains uncertain whether all domains/contexts of PA and SB are similarly associated with executive function and academic achievement. Objective: We investigated the prospective associations of accelerometer-measured 24h- movement behaviours and domain-specific PA and SB with executive function and academic achievement among school-aged children in Singapore. Methods: The Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort used a wrist-worn accelerometer (Actigraph-GT3x+) to measure 24h-movement behaviours data at ages 5.5 and 8 years. Executive function and academic achievement were assessed using NEuroPSYchology (NEPSY) and Wechsler Individual Achievement Tests at ages 8.5 and 9-years, respectively. Compositional data analyses were conducted to explore the associations of 24h-movement behaviour with outcomes, and multiple linear regression models to examine the associations of domain-specific PA and SB with outcomes (n=432). Results: Among 432 children whose parents agreed to cognitive assessments (47% girls and 58% Chinese), the composition of 24h-movement behaviours at ages 5.5 and 8 years was not associated with executive function and academic achievement. However, higher moderate-to-vigorous PA (MVPA) relative to remaining movement behaviours at age 5.5 years was associated with lower academic achievement [Mean difference (95% confidence interval): -0.367 (-0.726, -0.009) z-score], and reallocating MVPA time to sleep showed higher academic achievement scores [30 minutes from MVPA to sleep: 0.214 (0.023, 0.404) z-score]. Certain domains of PA and SB, notably organised PA/sports, outdoor play, and reading books were favourably associated with outcomes of interest, while indoor play and screen-viewing were unfavourably associated. Conclusion: The associations between movement behaviours and cognitive outcomes are multifaceted, influenced by specific domains of PA and SB. This study underscores the importance of participation in organised PA/sports, outdoor active play, and reading books, while ensuring adequate sleep and limiting screen viewing, to enhance cognitive outcomes. These findings underscore the need for further research into time-use trade-offs.